PI3K/AKT signaling is essential for communication between tissue-infiltrating mast cells, macrophages, and epithelial cells in colitis-induced cancer - Khan, Mohammad Wasim Kayyum; Keshavarzian, Ali; Gounaris, Elias; Melson, Joshua E.; Cheon, Eric C.; Blatner, Nichole R.; Chen, Zongmin E.; Tsai, Fu-Nien; Lee, Goo; Ryu, Hyunji; Barrett, Terrence A.; Bentrem, David J.; et al. (Clinical cancer research, 2013)
Purpose: To understand signaling pathways that shape inflamed tissue and predispose to cancer is critical for effective prevention and therapy for chronic inflammatory diseases. We have explored phosphoinositide 3-kinase (PI3K) activity in human inflammatory bowel diseases and mouse colitis models. - Experimental Design: We conducted immunostaining of phosphorylated AKT (pAKT) and unbiased high-throughput image acquisition and quantitative analysis of samples of noninflamed normal colon, colitis, dysplasia, and colorectal cancer. Mechanistic insights were gained from ex vivo studies of cell interactions, the piroxicam/IL-10−/− mouse model of progressive colitis, and use of the PI3K inhibitor LY294002. - Results: Progressive increase in densities of pAKT-positive tumor-associated macrophages (TAM) and increase in densities of mast cells in the colonic submucosa were noted with colitis and progression to dysplasia and cancer. Mast cells recruited macrophages in ex vivo migration assays, and both mast cells and TAMs promoted invasion of cancer cells. Pretreatment of mast cells with LY294002 blocked recruitment of TAMs. LY294002 inhibited mast cell and TAM-mediated tumor invasion, and in mice, blocked stromal PI3K, colitis, and cancer. - Conclusion: The PI3K/AKT pathway is active in cells infiltrating inflamed human colon tissue. This pathway sustains the recruitment of inflammatory cells through a positive feedback loop. The PI3K/AKT pathway is essential for tumor invasion and the malignant features of the piroxicam/IL-10−/− mouse model. LY294002 targets the PI3K pathway and hinders progressive colitis. These findings indicate that colitis and progression to cancer are dependent on stromal PI3K and sensitive to treatment with LY294002. Clin Cancer Res; 19(9); 2342-54. ©2013 AACR.
Gesehen am 29.04.2021